Probing cations recognized by a crown ether with the 3D-RISM theory. II. 18-crown-6 ether - Maruyama, Y.; Matsugami, M.; Ikuta, Y. (Condensed Matter Physics, 2007)
In the previous study, we investigated the cation recognition by 12-crown-4 ether with the 3D-RISM theory [Ikuta, Y. et al., Chem. Phys. Lett., 2007, 433, 403], and showed the applicability of the theory to the problem. The results show that a 12-crown-4 ether recognizes Li⁺ and Mg²⁺. 18-crown-6 ether is widely used in comparison with 12-crown-4 ether. In this study, we calculated three-dimensional distributions of water as well
as cations (Li⁺, K⁺, Mg²⁺, Ca²⁺) inside and outside 18-crown-6 ether in aqueous solutions of electrolytes. A 18-crown-6 ether recognizes not only Li⁺ and Mg²⁺ but also K+ and Ca²⁺. K⁺ is dehydrated in the host cavity whereas other cations are hydrated. It is found that a hydration structure, as well as cation size, is important for the molecular recognition by crown ether. В попереднiх дослiдженнях ми вивчали в рамках теорiї ЗD-RISM катiонне впiзнавання 12–корона–4 ефiром [Ikuta, Y. et al., Chem. Phys. Lett., 2007, 433, 403] i показали застосованiсть цiєї теорiї. Результати показують, що 12-корона-4 ефiр впiзнає iони Li⁺ i Mg²⁺. 18-корона-6 ефiр ширше використовується порiвняно з 12-корона-4 ефiром. В данiй роботi розраховано тривимiрнi функцiї розподiлу води вiдносно iонiв Li⁺, K⁺, Mg²⁺, Ca²⁺ в серединi та зовнi 18-корона-6 ефiру у водних розчинах електролiту. Показано, що 18-корона-6 ефiр впiзнає не тiльки iони Li⁺ i Mg²⁺, але також iони K⁺ i Ca²⁺. K⁺ всерединi порожнини дегiдратується, тодi як iншi катiони є гiдратованими. Встановлено, що гiдратацiйна структура та катiоннi розмiри є важливими для молекулярного впiзнавання коронним ефiром.